2020
DOI: 10.3390/coatings10070699
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Changes in Suspension Plasma-Sprayed TBCs Deposited on Complex Geometry Substrates

Abstract: Thermal barrier coatings (TBCs) are considered a promising solution for improving the efficiency of internal combustion engines. Among the thermal spray processes, the relatively newly developed suspension plasma spray (SPS) is an attractive candidate due to its unique microstructural features that have already demonstrated increased performance in gas turbine applications. To achieve these features, thermal spray conditions play an essential role. In specific uses, such as piston of diesel engines, parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Figures 10 and 11 shows micrographs of the microstructure of top coats sprayed with the same parameters on buttons and pistons from a light-duty diesel engine (Region Cc-L and Cx-M) previously studied by the authors (Ref 26). Similar microstructures were identified, but some differences were observed because of the piston shape's influence on the plasma streamlines (Ref 23,40,45).…”
Section: Top Coat Microstructurementioning
confidence: 64%
See 1 more Smart Citation
“…Figures 10 and 11 shows micrographs of the microstructure of top coats sprayed with the same parameters on buttons and pistons from a light-duty diesel engine (Region Cc-L and Cx-M) previously studied by the authors (Ref 26). Similar microstructures were identified, but some differences were observed because of the piston shape's influence on the plasma streamlines (Ref 23,40,45).…”
Section: Top Coat Microstructurementioning
confidence: 64%
“…This condition could be associated with piston applications. In previous work (Ref 23), the authors investigated different microstructures produced on automotive pistons and the physical properties of the coatings. However, a systematic study with defined spray angles and coating property evaluation has yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Further, continuously reinforced concrete pavement α correlation with spalling, performance and mechanical behavior is also studied with OOF2 and results are compared with commercial FE software [27]. Furthermore, the λ and thermal effusivity are simulated for the different regions of TBCs as synthesized by thermal spray processes and suspension plasma spray for gas turbine applications [28]. It was found that modeling provides good results [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the λ and thermal effusivity are simulated for the different regions of TBCs as synthesized by thermal spray processes and suspension plasma spray for gas turbine applications [28]. It was found that modeling provides good results [28]. Moreover, Si 3 N 4 welding with 316L stainless steel is designed using Mo/Ag composite as interlayer and the residual tensile stress in the interlayer is performed [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation